2018
DOI: 10.7554/elife.34519
|View full text |Cite
|
Sign up to set email alerts
|

A new mode of pancreatic islet innervation revealed by live imaging in zebrafish

Abstract: Pancreatic islets are innervated by autonomic and sensory nerves that influence their function. Analyzing the innervation process should provide insight into the nerve-endocrine interactions and their roles in development and disease. Here, using in vivo time-lapse imaging and genetic analyses in zebrafish, we determined the events leading to islet innervation. Comparable neural density in the absence of vasculature indicates that it is dispensable for early pancreatic innervation. Neural crest cells are in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 66 publications
3
27
0
Order By: Relevance
“…Consistent with this possibility, it was recently shown that the embryonic zebrafish islet is innervated at the relevant time points, and that a neurotransmitter, namely galanin expressed in these neurons, is involved in blood glucose regulation. 59,60 Notably, the delayed glucose response in the isolated zebrafish islets is similar to that seen in mammalian islets. While this delay is attributed to the time taken for glucose diffusion and metabolism, 61,62 it might be further affected by the cleavage of neural connection during the islet isolation procedure.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with this possibility, it was recently shown that the embryonic zebrafish islet is innervated at the relevant time points, and that a neurotransmitter, namely galanin expressed in these neurons, is involved in blood glucose regulation. 59,60 Notably, the delayed glucose response in the isolated zebrafish islets is similar to that seen in mammalian islets. While this delay is attributed to the time taken for glucose diffusion and metabolism, 61,62 it might be further affected by the cleavage of neural connection during the islet isolation procedure.…”
Section: Discussionmentioning
confidence: 68%
“…While this delay is attributed to the time taken for glucose diffusion and metabolism, 61,62 it might be further affected by the cleavage of neural connection during the islet isolation procedure. 60 Measurements of real-time glucose response of pancreatic mouse islets by autofluorescence NAD(P)H signals also suggests that there might be differences in glucose metabolism after isolation. 63 However, the time to reach the initial GCaMP fluorescence peak after glucose injection in mice in vivo (~1-2 minutes) is still much test) (D) Quantification of GCaMP6s fluorescence intensity ex vivo in wild-type and Ca V 1.2 mutant larvae shown as area under curve (AUC) upon 2 mM and 20 mM glucose stimulation normalized to the treatment duration (n = 9 and 10 larvae, respectively) (***p < 0.0005, two-tailed, unpaired t-test).…”
Section: Discussionmentioning
confidence: 99%
“…The large volume of innervated islets is in accordance with a role for neural signals in islet development and maintenance. In both mice and zebrafish, β cells aggregate close to pancreatic nerves in development, and islet architecture is disrupted by loss of neural signals ( 55 , 56 ). There is also close physical association between nerves and islets in human embryos, particularly in the middle and late trimester, when there is rapid development of the endocrine pancreas ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…41,[57][58][59] For example, events leading to the innervation of the pancreas are being determined efficiently due to transparent embryos and external development of the fish. 60 Furthermore, the emerging field of metabolomics has made its way into zebrafish and will further contribute in bridging the gap between genotype and phenotype and from bench to bedside. 61,62 Goby, tilapia and perch Some other non-traditional fish models have also been tested as models for diabetes, and in some cases the work precedes the work using zebrafish.…”
Section: Future Of Zebrafish In Metabolic Disease Researchmentioning
confidence: 99%
“…Effects of the microbiome on metabolism or the effects of inputs from the nervous system to tissues like the liver and fat are being studied, and research into how this affects metabolism is picking up with accelerated pace . For example, events leading to the innervation of the pancreas are being determined efficiently due to transparent embryos and external development of the fish …”
Section: Future Of Zebrafish In Metabolic Disease Researchmentioning
confidence: 99%